Bhutan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper describes the current tax system in Bhutan and suggests options for tax policy reform. Though significant hydropower revenues are expected in the medium term as major projects come on-stream, reforms to the existing tax system in the interim will generate fiscal room and prevent recourse to domestic debt to finance development needs. Key reforms include reducing tax exemptions in the near term and introduction of value-added tax in the medium term. The paper also analyzes the adequacy of international reserves in Bhutan using a customized risk-weighted metric. The results indicate that Bhutan's reserve levels are ample.